(untitled) (Al-Academy, 2024)
The formal changes in the graphic designs come according to the determinants of the visual visual formation of the output of the design elements, which depend in their structure on work mechanisms that stem from the design idea and end with the processes formulated in the visual field. Which governs the appearance of the formal change because it relies on the principle of the external and the external in its patterns and formations. Thus, a group of formal changes to the general appearance of the design achievement can be related to the design industry, and change is governed by several factors and influences that contribute to the establishment of new relationships between the components or elements of the design achievement. Therefore, the design must It is in contact with its environment, culture, heritage and beliefs, which in turn contribute to the crystallization and embodiment of its stylistic features that coincide with temporal and spatial shifts in the development of designs, as well as the presence of incentives for building blocks that work to develop its style and its creative transformation, especially since the creative change is linked to the aesthetic taste of the era represented by the values, ideals and beliefs found in A specific environment that the designer employs while receiving him through his feelings and translating them in a way that suits his culture and inclinations, and the new incentive is the determinant of the content of the design work.The research included conclusions, including the following: This change in concepts and terminology was reflected positively in the artistic and literary field and in design, which acquired new concepts, including pre-modernity, modernity, and post-modernism, and were accompanied by some trends, including structuralism, semiotics, and deconstruction, and design institutions took knowledge circles from them. In radical change and change in dealing with topics and liberation from previous restrictions.